Precipitation of Calcite during the Deposition of Paleogene Sangkarewang Oil Shale, Ombilin Basin, West Sumatra, Indonesia - Widayat, Agus Haris; Anggayana, Komang; Khoiri, Isra (Geological Agency, 2015)
DOI: 10.17014/ijog.2.3.185-197Geochemical and petrographical analyses were carried out to investigate the occurrence of calcite in theformer Ombilin lacustrine lake. The study involves eight samples taken from a 56 m long drill core of Sangkarewangoil shale. Geochemical investigation showed that the samples consist of varied terrigenous input represented by Si, Al, K, and Ti, and autochthonous input represented by S, total organic carbon (TOC), and d13C of bulk organic matter. Along the drill core profile the abundance of autochthonous input decreases upwards, while that of terrigenous input oppositely increases upwards. Petrographical analysis revealed that calcite is a major mineral in the samples. In this study, the abundance of calcite could be represented by the abundance of Ca, as calcite is the only significant Ca containing mineral. Ca is abundant in the samples (8.4% in average) and its concentration varies similarly with those of S, TOC, and d13C, suggesting that the element as well as calcite incorporates the autochthonous input. Thevariation of calcite abundance in the drill core profile is considered to be related with primary productivity changes during the development of the former lake. Higher primary productivity represented by more positive of d13C value(-24.8‰) during the deposition of the lower part of the drill core profile promoted the higher amount of deposited organic matter. In such environment, the supersaturation of carbonate ion in lake water was also reached and significant precipitation of authigenic calcite occurred. As the lake developed, the primary productivity decreased as indicated by more negative of d13C value (eventually -26.8‰). This condition led to the decreases of deposited organic matterand calcite in the lake sediments.